(untitled) (Journal of Partial Differential Equations, 2020)
In this paper, we study the asymptotic behavior of global smooth solution to the initial boundary problem for the 1-D energy transport model in semiconductor science. We prove that the smooth solution of the problem converges to a stationary solution exponentially fast as t → ∞ when the initial data is a small perturbation of the stationary solution.